Human small bowel as model for poisoning with organophosphorus compounds. (June 2019) - Marquart, Katharina; Prokopchuk, Olga; Wilhelm, Dirk; Worek, Franz; Thiermann, Horst; Martignoni, Marc E.; Wille, Timo
Abstract: In previous experiments, human and rat small bowel samples have been successfully used to study the spasmolytic effect of (potential) therapeutics in carbamate-constricted bowel specimens. Additionally, transferability from rat to human data was shown in the previous study. In the present study, the effects of atropine, scopolamine, MB327, HI-6 as well as obidoxime were examined in organophosphorus-poisoned human small bowel specimens. All substances were tested with at least seven concentrations in samples previously exposed to the nerve agent sarin. Furthermore, the cholinesterase reactivation potential of all substances was investigated. The test substances displayed a spasmolytic effect allowing the calculation of dose-response curves and EC50 s. The parasympatholytic compound scopolamine had the strongest relaxing effect (EC50  = 0.05 μM) followed by atropine (EC50  = 0.07 μM). HI-6 and obidoxime were capable to reactivate the sarin-inhibited cholinesterase activity in small bowel samples. Both substances restored AChE activity in a dose-dependent way, with HI-6 being more potent (HI-6 EC50  = 3.8 μM vs obidoxime EC50  = 197.8 μM). Summarizing, our isolated human small bowel setup is a suitable tool to investigate the smooth muscle relaxing effect of (candidate) therapeutics for organophosphorus compound poisoning i.e. sarin exposure in a complex 3D tissue model. Highlights: Human small bowel exposed to sarin resulted in an irreversible smooth muscle contraction. All candidate and approved therapeutics displayed a dose-dependent smooth muscle relaxing effect after sarin exposure. Scopolamine and atropine showed the most pronounced smooth muscle relaxing effect. HI-6 and obidoxime fully restored sarin-inhibited cholinesterase activity.